Dclk1, a tumor stem cell marker, regulates pro-survival signaling and self-renewal of intestinal tumor cells - Chandrakesan, Parthasarathy (Mol Cancer, 2017)
BACKGROUND: More than 80% of intestinal neoplasia is associated with the adenomatous polyposis coli (APC) mutation. Doublecortin-like kinase 1 (Dclk1), a kinase protein, is overexpressed in colorectal cancer and specifically marks tumor stem cells (TSCs) that self-renew and increased the tumor progeny in Apc (Min/+) mice. However, the role of Dclk1 expression and its contribution to regulating pro-survival signaling for tumor progression in Apc mutant cancer is poorly understood. METHODS: We analyzed DCLK1 and pro-survival signaling gene expression datasets of 329 specimens from TCGA Colon Adenocarcinoma Cancer Data. The network of DCLK1 and pro-survival signaling was analyzed utilizing the GeneMANIA database. We examined the expression levels of Dclk1 and other stem cell-associated markers, pro-survival signaling pathways, cell self-renewal in the isolated intestinal epithelial cells of Apc (Min/+)mice with high-grade dysplasia and adenocarcinoma. To determine the functional role of Dclk1 for tumor progression, we knocked down Dclk1 and determined the pro-survival signaling pathways and stemness. We used siRNA technology to gene silence pro-survival signaling in colon cancer cells in vitro. We utilized FACS, IHC, western blot, RT-PCR, and clonogenic (self-renewal) assays. RESULTS: We found a correlation between DCLK1 and pro-survival signaling expression. The expression of Dclk1 and stem cell-associated markers Lgr5, Bmi1, and Musashi1 were significantly higher in the intestinal epithelial cells of Apc (Min/+)mice than in wild-type controls. Intestinal epithelial cells of Apc (Min/+)mice showed increased expression of pro-survival signaling, pluripotency and self-renewal ability. Furthermore, the enteroids formed from the intestinal Dclk1(+) cells of Apc (Min/+)mice display higher pluripotency and pro-survival signaling. Dclk1 knockdown in Apc (Min/+) mice attenuates intestinal adenomas and adenocarcinoma, and decreases pro-survival signaling and self-renewal. Knocking down RELA and NOTCH1 pro-survival signaling and DCLK1 in HT29 and DLD1 colon cancer cells in vitro reduced the tumor cells’ ability to self-renew and survive. CONCLUSION: Our results indicate that Dclk1 is essential in advancing intestinal tumorigenesis. Knocking down Dclk1 decreases tumor stemness and progression and is thus predicted to regulate pro-survival signaling and tumor cell pluripotency. This study provides a strong rationale to target Dclk1 as a treatment strategy for colorectal cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12943-017-0594-y) contains supplementary material, which is available to authorized users.